The promised Neverland. 6, B06-32 - Shirai, Kaiu (Shonen Jump manga., 2018)
The children have successfully escaped Grace Field House, but their troubles are just beginning. Now up against a dangerous natural world and their demon pursuers, Emma and Ray struggle to lead the children to safety. Just when the situation is at its most dire, a mysterious girl suddenly appears. Is she there to help, or is it a demonic trap...? -- <U+01C2>c from Amazon.com